Patterns of resource utilization and mental health symptoms among women exposed to multiple types of victimization: a latent class analysis. - Young-Wolff, Kelly C; Hellmuth, Julianne; Jaquier, Veronique; Swan, Suzanne C; Connell, Christian; Sullivan, Tami P (Journal of interpersonal violence, 2013)
Although the value of resources aimed to support women who experience intimate partner violence (IPV) is clear, few studies have investigated how exposure to multiple types of victimization influences women's resource utilization. We applied latent class analysis (LCA) to a sample of 412 women who used IPV in their current relationships to test whether women's resource utilization is associated with different patterns of victimization, including current IPV victimization, past IPV victimization, and childhood victimization. Three classes of women were identified: the Low Cumulative IPV class (n = 121) included women with a low prevalence of past IPV victimization and low severity of current IPV victimization; The High Past/ Low Current IPV class (n = 258) included women with a high prevalence of past IPV victimization but low severity of current IPV victimization; and the High Cumulative IPV class (n = 33) included women with a high prevalence of past IPV victimization and severe current IPV victimization. Multiple types of childhood victimization were highly prevalent among women in all three classes. Women in the High Cumulative IPV class used a greater variety of resources, experienced a greater number of posttraumatic stress and depression symptoms, drug problems, and used more severe IPV aggression compared to women in other classes. These findings highlight the heterogeneity of resource utilization among women in relationships characterized by bidirectional IPV and underscore the potential clinical utility of adapting services to meet the specific needs of women with unique profiles of victimization.
Keywords: Adolescent; Adult; Crime Victims; Female; Health Resources; Humans; Interpersonal Relations; Mental Health; Middle Aged; Sexual Partners; Young Adult